THE EFFECTS OF RUSSIA – UKRAINE WAR ON AFRICA ECONOMY - Adogbeji, Elvis Oghenenyerhovwo; Clark, Esekumemu Victor; Ejogba, Orhero Abraham (EBSU Journal of Social Sciences and Humanities, 2024)
The Russia-Ukraine war carries implications that extend beyond the immediate conflict zone, impacting various facets of the African economy. This paper delves into the potential effects of this geopolitical turmoil on the broader African economic. Thus, the thrust of this paper is to identify the various effects the ongoing war between Russia and Ukraine will have on Africa economy. The study adopted historical method as data are sourced from secondary sources such as publications, journals, textbooks and online. The study finds that the ongoing war is having mostly negative effects on Africa economy such as increase in price of grain in Africa due to break down in importation of grain from Ukraine, drastic downturn in abroad remittance, reduction in FDI amongst others. The study suggest that Africa policymakers, economists, and other stakeholders should seize the opportunity to negotiate better economic interest of Africa in the international scene. Also, agricultural investment commitment should be revisited amongst others.